The limitations of dispositional resistance in relation to organizational change - Michel, Alexandra; By, Rune Todnem; Burnes, Bernard (Management decision, 2013)
Purpose - The purpose of this research is to test the moderating role of dispositional resistance in achieving sustainable organisational change. Design/methodology/approach - Four studies were conducted in the period 2005‐2007. Each study included the participation of individuals experiencing ongoing organisational changes at the time, and was repeated with an independent sample in order to strengthen the meaning of the findings. Findings - The studies confirmed the assumed positive relationship between benefit of change and commitment to change. Furthermore, two studies confirmed the assumed negative relationship between extent of change and commitment to change, while the other two studies, in contrast to the hypothesis presented, found a positive relationship. Despite the assumptions, with the exception of one study it was not possible to show moderating effects of resistance to change. Research limitations/implications - The study casts doubt about resistance to change defined as a disposition and its stability across different contexts. In explaining these results, the authors draw on Lewin's work on resistance to change. Originality/value - The paper argues that the importance of dispositional resistance is that it predisposes individuals to view change in a particular way, either negatively or positively. However, the level of resistance towards a specific change event will be influenced by other factors, noticeably the organizational context and the way the change is managed. Consequently, the importance of dispositional resistance lies in its ability to influence an organization's readiness for change and to identify the level of resistance it might expect to meet, and thus the approach to change it needs to adopt.